Emerging Biomarkers for Prediction and Early Diagnosis of Necrotizing Enterocolitis in the Era of Metabolomics and Proteomics - Agakidou, Eleni; Agakidis, Charalampos; Gika, Helen; Sarafidis, Kosmas (Frontiers in Pediatrics, 2020)
Necrotizing Enterocolitis (NEC) is a catastrophic disease affecting predominantly premature infants, characterized by high mortality and serious long-term consequences. Traditionally, diagnosis of NEC is based on clinical and x-rays findings, which nonetheless are non-specific for NEC, thus perplexing differential diagnosis from other conditions such as neonatal sepsis and spontaneous intestinal perforation. In addition, by the time clinical and x-ray findings appear, NEC has already progressed to an advanced stage. During the last 3 decades, a lot of research has been dedicated to the discovery of biomarkers, that could accurately predict and early diagnose NEC. Biomarkers used thus far in clinical practice include acute phase proteins, inflammation mediators, and molecules involved in immune response. However, none has been proven accurate enough to predict and early diagnose NEC or discriminate clinical from surgical NEC or other non-NEC gastrointestinal diseases. Complexity of mechanisms involved in NEC pathogenesis, which largely remain poorly elucidated, could partly explain the unsatisfactory diagnostic performance of the existing NEC biomarkers. More recently applied molecular technics can provide important insights into the pathophysiological mechanisms underlying NEC but also aid in the detection of potentially predictive, early diagnostic, and prognostic biomarkers. Progress in omics technology has allowed for the simultaneous measurement of a large number of proteins, metabolic products, lipids, and genes, using serum/plasma, urine, feces, tissues, and other biological specimens. This review is an update of current data on emerging NEC biomarkers detected by the use of proteomics and metabolomics, further discussing limitations and future perspectives in prediction and early diagnosis of NEC.